Entrance Botanic Gardens - (:unkn) unknown (Waterman the Hatter, Clothier and Outfitter, Trinidad, 2010)
A picture of the entrance to the Botanical Gardens, Port of Spain, Trinidad.
Colour: Black and white, green; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Donkeys--Trinidad and Tobago; Cycling--Trinidad and Tobago